Sexual Dysfunction Among Males Receiving Psychotropic Medication: A Cross-Sectional Study - Singh, Lakshman (Journal of Biomedical and Pharmaceutical Research, 2018)
Sexual dysfunction is a common and often overlooked side effect of psychotropic medications. This study aims to evaluate the prevalence and nature of sexual dysfunction among male patients receiving psychotropic drugs for various mental health conditions. A total of 100 male patients, aged 18-60 years, undergoing treatment with antidepressants, antipsychotics, and mood stabilizers, were included in the study. Patients were assessed using the International Index of Erectile Function (IIEF) and the DSM-V criteria for sexual dysfunction. The results showed that approximately 45% of the participants experienced some form of sexual dysfunction, including erectile dysfunction (ED), decreased libido, and premature ejaculation. Antidepressants were found to have the most significant impact on sexual function, followed by antipsychotics. The findings suggest that sexual dysfunction should be regularly assessed in male patients taking psychotropic medications and that management strategies should be considered to improve quality of life. Keywords: Sexual dysfunction, psychotropic medications, erectile dysfunction, antidepressants, antipsychotics, males.